Analisis Pengintegrasian Pendidikan Mitigasi Bencana Pada Pembelajaran di Indonesia - Yani Yani; Enok Maryani; Ahmad Yani (UM Purwokerto Press, 2024)
Indonesia is a country that faces a high threat of natural disasters. The resulting losses are significant. Therefore, systematic steps are needed to analyze and reduce the factors causing disasters. Efforts to reduce disaster risks include integrating disaster mitigation education into multiple subjects and at every level of education. So far, disaster education has only been partially implemented, with only science, social studies, and geography lessons incorporating disaster content. Other subjects have not yet integrated disaster into their curriculum. This article aims to explain the integration of disaster mitigation education in schools to cultivate a generation of citizens who are aware and capable of adapting to disasters in their surroundings. The research method employed in this study is a literature review using the Population, Intervention, Comparison, and Outcome (PICO) technique. The search and selection procedures for articles in this study utilize the Preferred Reporting Items for Systematic Reviews & Meta-analyses (PRISMA) framework. The study involves an analysis of relevant sources related to the integration of disaster education. Integrating disaster mitigation education into various subjects will foster a culture of disaster preparedness, thereby minimizing the risks posed by disasters. When students are equipped to face disasters, they can develop resilience towards the disasters they encounter.